Association Between IL-28B (rs8099917) and IL-28B (rs12979860) with Predisposition to Diseases Related to the HTLV-1: Systematic Review and Meta-Analysis - Naomi Cuenca; Damarys Cordero; Brenda López-Ulloa (Pathogens)
This research addresses IL-28B gene polymorphisms (rs12979860 and rs8099917) to determine their association with HTLV-1-related diseases; it aims to compare genotypic frequencies to identify predisposition or protection, considering population, disease, and controls. Given HTLV-1’s impact on immunity, this study seeks biomarkers for early diagnosis and intervention. A systematic search met inclusion criteria, such as open access bibliographic and experimental studies published in English between 2010 and 2024, and genetic factors linked to susceptibility to pathologies. Regarding exclusion criteria, bibliographic or experimental studies in organisms other than humans, unofficial sources, non-indexed journals, and scientific articles in languages other than English were ruled out. Statistical data analyses were assessed using meta-analysis, including forest plot and Q test of heterogeneity based on the I2 statistics. The analyzed data indicate associations between genotypes, such as CT, GG, CC, and TT of the rs12979890 and rs8099917 polymorphisms and the predisposition to various diseases, such as HCV, arthropathy, HAM/TSP, cytomegalovirus and Crimean–Congo hemorrhagic fever associated with HTLV-1; however, the observed inconsistencies, such as high heterogeneity, and deficiency of related information limit the consolidation of the findings. Further research is needed to clarify IL-28B genotype interactions and disease susceptibility in HTLV-1 infections.